2018
DOI: 10.1001/jamaophthalmol.2018.3963
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Scholarly Opportunities for Medical Students and Residents in Professional Ophthalmology Organizations

Abstract: How can we enrich the educational experience of medical students despite a steady decrease in ophthalmology content and exposure in the standard medical school curriculum? 1 We report a range of educational and scholarly opportunities offered by professional US ophthalmology organizations that may potentially be used to complement formal clinical teaching and maximize exposure to ophthalmology.Methods | Two investigators (A.Y. and X.Z.) independently reviewed the websites and bylaws of 17 major national ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Organizational reviews for other specialties have been conducted. [33][34][35]39 Specifically, national otolaryngology organizations demonstrated an average membership fee of $73 (±$30) for medical students and an average conference fee of $366 (±300). An ophthalmology review found an average membership fee of $43 and a mean conference registration cost of $307 for students.…”
Section: Conference Presentation Registration Fees and Travel Scholar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational reviews for other specialties have been conducted. [33][34][35]39 Specifically, national otolaryngology organizations demonstrated an average membership fee of $73 (±$30) for medical students and an average conference fee of $366 (±300). An ophthalmology review found an average membership fee of $43 and a mean conference registration cost of $307 for students.…”
Section: Conference Presentation Registration Fees and Travel Scholar...mentioning
confidence: 99%
“…32 Although exposure to plastic surgery continues to be an institutional-level issue, no studies have assessed the landscape of students' exposure to plastic surgery at state, regional or national levels. [33][34][35] This study examines available opportunities related to professional development, academic leadership, and research engagement through national plastic surgery organizations within the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The VHRN sets itself apart from other professional organizations in vision research by its demonstrable commitment to the professional development of its 288 diverse trainees, including post-doctoral fellows, graduate students, undergraduate students, medical students, ophthalmology residents, optometry students and trainees in vision rehabilitation. A study by Yang et al examining the opportunities for medical students within the major American professional bodies in ophthalmology revealed that only 24% of these groups granted membership to medical students, and that only 12% of the studied groups had student positions within committees [2]. In contrast, the VHRN actively encourages student and trainee involvement.…”
Section: Participation Of Trainees In Vhrnmentioning
confidence: 99%
“…Future physicians may be unaware of these opportunities available to them. Current studies have explored trainee involvement within American professional organizations of various medical specialties, including dermatology, 1 orthopedic surgery, 2 otolaryngology, 3 ophthalmology, 4 and radiology. 5 However, the level of involvement of trainees in Canadian professional organizations to our knowledge has yet to be described in the literature.…”
Section: Introductionmentioning
confidence: 99%